The Efficiency of Application of Social Media in History Learning at Junior High School - Jumardi Jumardi; Andi Andi; Hari Naredi (STAI Hubbulwathan Duri, 2023)
Using the appropriate learning resources is crucial to making progress towards one's educational objectives. The use of electronic resources for education increased during the Covid-19 epidemic. Because of this, educational technology in Indonesia can now develop in a new direction. This research aimed to evaluate the efficacy of using social media apps to teach history in the classroom. Quantitative research methods and testing procedures were used in this investigation. Fifty instructors participated in the study, representing Bandar Lampung, Bekasi, East Jakarta, Bogor Regency, and Tangerang City schools. There are 22 male instructors and 28 female teachers across the 24 elementary schools, 14 middle schools, and 11 high schools. History classes also make use of digital learning materials. Methods of descriptive quantitative research. The theoretical study of history can establish and foster a sense of nationalism in the younger generation. Hence history education plays an important role. However, a student-friendly learning medium is required to transmit the theoretical study knowledge.